On Roots and Burial. - Wampole, Christy (Substance: A Review of Theory & Literary Criticism, 2025)
The article focuses on how metaphors of roots and burial reflect evolving relationships to ancestry, place, and death in an era shaped by globalization and ecological disruption. Topics include the symbolic and literal dislocation of familial roots, the environmental degradation of ancestral lands, and the egalitarian anonymity imposed by modern burial practices such as those seen in the Paris Catacombs.